Gamma-rays from AGN in dwarf galaxies - Carlos, Douglas Ferreira (2023)
Understanding the physics and demographics of black holes (BHs) in the intermediate-mass regime can lead us to a better understanding of the processes of AGN feedback, BH-galaxy co-evolution, and even shed light on the mechanisms that formed the seeds of todays supermassive black holes. A promising approach to learn about the activity of the elusive intermediate-mass BHs is to look for their high energy emission in nearby dwarf galaxies. In this work we have used 13 years of data from the Large Area Telescope (LAT) aboard the Fermi spacecraft and implemented a stacking analysis to look for possible -rays from a 135 dwarf galaxies exhibiting signatures of AGN activity in different parts of the electromagnetic spectrum. With our stacking technique, we find that dwarf AGN as a population are significant -ray emitters even though most objects are individually too faint. Two target galaxies constitute strong candidates for -ray sources, both represent 4 excesses and have luminosities of up to 10^ erg/s. We explore possible correlations involving the luminosities of our dwarf AGN population and find the two strongest candidates are too bright when compared to the -ray activity expected from their host galaxys star formation rates, suggesting the AGN contribution to this band is surpassing that of typical stellar processes. The large values of for the best candidates also raises the possibility that their emission has its origin in hitherto undetected relativistic jets.